PSYCHOLOGICAL ASSOCIATION OF MOBILE GAMES AND CHILDREN’S WELLBEING ^ - R, Bharath Yuvaraj; D, Jayaprakash (International Journal of Psychosocial Rehabilitation, 2020)
Video gaming is one of the main free time physiomental exercises often performed by people to get away from boredom. Though it is the activity done by people of all age groups but mostly children practice it a lot compared to their elders. As per the report of statistica.com, the daily time users spend on their devices grew drastically to 215 minutes in 2018 which was just 152 minutes in 2014. This daily device time is expected to grow 234 minutes in 2021. The same report states that 50% of the time spent on the internet was through mobile phones [1]. There is a huge percentage of users who are children as mobile phone users. Mobile gaming is the 50 billion industry. Far bigger than Hollywood’s worldwide box office revenue of 40 billion as per the survey of medium.com [2]. Children play an important role in revenue growth. The maximum percentage of game users are children. Games have a huge psychological effect on the body, mind, and soul. Games are designed to perform the tasks which are not possible, righteous, or mostly unethical in intellectual social structure. The killing law and authority disrespect, sexual exploitation, foul language, and gesture, racial stereotypes are quite common and performed with great comfort in mobile gaming [3]. Recently several Hindu religion god and goddesses were used in games performing immoral acts in games. All these works are done to make the games look much violent, realistic and thrilling. Compared to grownups, youth and children are way susceptible to such thrills so they are mainly the prime target to such obscene gaming experience. Our paper deals with brief research over such issues as per children’s context. We examine the real-time parameters with special consideration on children about the mental standing with the games’ perspective. The mental physical and social aspects are planned to be reviewed extensively. We also plan to take necessary remedial actions to aware of the children and their parents against the threat of gaming which is considered underrated worldwide.